Torsional characteristics of single walled carbon nanotube with water interactions by using molecular dynamics simulation - Vijayaraghavan, V. (2014)
The torsional characteristics of single walled carbon nanotube (SWCNT) with water interactions are studied in this work using molecular dynamics simulation method. The torsional properties of carbon nanotubes (CNTs) in a hydrodynamic environment such as water are critical for its key role in determining the lifetime and stability of CNT based nano-fluidic devices. The effect of chirality, defects and the density of water encapsulation is studied by subjecting the SWCNT to torsion. The findings show that the torsional strength of SWCNT decreases due to interaction of water molecules and presence of defects in the SWCNT. Additionally, for the case of water molecules encapsulated inside SWCNT, the torsional response depends on the density of packing of water molecules. Our findings and conclusions obtained from this paper is expected to further compliment the potential applications of CNTs as promising candidates for applications in nano-biological and nano-fluidic devices.